Inhibition of Transketolase Improves the Prognosis of Colorectal Cancer - Zhang, Linhao; Huang, Zhiyin; Cai, Qiuyu; Zhao, Chong; Xiao, Yang; Quan, Xin; Tang, Chengwei; Gao, Jinhang (Frontiers in Medicine, 2022)
Colorectal cancer (CRC) remains a heavy health burden worldwide. Transketolase (TKT) is a crucial enzyme in the non-oxidative phase of the Pentose Phosphate Pathway (PPP), and is up-regulated in multiple cancer types. However, the role of TKT in the prognosis of CRC remains unclear. We aimed to explore whether TKT expression is altered in CRC, how TKT is associated with the prognosis of CRC, and whether the regulation of TKT might have an impact on CRC. Differentially expressed genes (DEGs) were identified using bioinformatics analysis. TKT expression was examined in the human colon adenocarcinoma tissue microarray and xenografts. Cell viability, proliferation, migration, and apoptosis assays in vitro were applied to evaluate the protumoral effects of TKT on CRC. TKT was found to be a risk factor for the poor prognosis of CRC by bioinformatics analysis among the DEGs. TKT was significantly up-regulated in colon adenocarcinoma tissues compared with normal colon tissues in patients. Moreover, similar results were found in HCT116 and RKO human colon adenocarcinoma xenografts in nude mice. TKT expression was positively associated with advanced TNM stage, positive lymph nodes, and poor 5 or 10-year overall survival of CRC patients. In vitro, inhibition of TKT reduced cell viability, proliferation, and migration, and induced cell apoptosis. In addition, inhibition of TKT decreased the protein levels of NICD and Hes1. In conclusion, high TKT expression was associated with the poor prognosis of CRC patients. The protumoral effects of downregulating TKT may be realized by suppressing the Notch signaling pathway. TKT may be a new prognostic biomarker and therapeutic target for CRC.